Status of Serum Magnesium level in Diabetic Retinopathy & Non Retinopathy in the Patients of Type-II Diabetes Mellitus - Memon, Ali Raza; Ahmadani, Rubina; Lighari, Jawaid Hussain; Memon, Muhammad Yousuf; Chandio, Sofia (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To compare the serum magnesium levels in normal population, non-complicated patients of type –II diabetes mellitus and complicated patients of type-II diabetes mellitus with retinopathy & to observe the role of serum magnesium in development of retinopathy in patients of type-II diabetes mellitus. METHODOLOGY: Total 100 subjects were recruited divided in to three groups, group A contain 30 normal subjects consider as control group, group B contain 35 diagnosed cases of type-II diabetes mellitus without retinopathy and group C contain 35 diagnosed cases of type –II diabetes mellitus with retinopathy. Random blood glucose level was measured by glucose oxidase method; serum magnesium level was measured on Zeeman spectrophotometer. All data was analyzed on SPSS 16 by applying independent student t-test. RESULTS: The Mean Random Blood Glucose level was significantly high (p<0.05) in diabetic patients with retinopathy as compared to with control and diabetic with non-retinopathy groups. The serum magnesium level was significantly (p<0.001) decline in patients of type –II diabetes mellitus with retinopathy as compared with control group and diabetes mellitus without retinopathy. CONCLUSION: The hypomagnesaemia is one of the provoking factor for the development of diabetic retinopathy along with poor glycemic control and long duration of type –II diabetes mellitus.